PENGEMBANGAN PANDUAN PRAKTIKUM ONLINE MENGGUNAKAN SMARTPHONE BERBASIS APLIKASI PHYPOX - Shelin Novitasari; Djeli Alvi Tulandi; Jimmy Lolowang (Charm Sains: Jurnal Pendidikan Fisika, 2021)
In today's digital era, the learning system has undergone many changes. Online-based learning has become one of the most important learning models today and one of the learning models that utilize online media such as Blended learning or the use of smartphones. The purpose of this research is to develop an online laboratory guide on pendulum material. The stages that have been carried out in this study: Designing an online laboratory activity guide using a phyphox application-based cellphone. This software development is carried out based on the research and development research collaboration of Research and Development (R & D) including: Analysis / Defining Stage, Design Stage, Development Stage, Testing and Evaluation Phase. The results of the study recommend that the online practicum guide using a phyphox application-based handphone on pendulum material is suitable for optimizing practicum activities in the Physics Department. This collaborative research between lecturers and students can also improve the academic climate, through optimizing lecturer-student interactions.